Changes in hemoglobin levels and cardiometabolic health in adults with metabolic syndrome – a secondary outcome analysis of a six-month randomized controlled trial - Gassner, Jasmina; Norha, Jooa; Sjöros, Tanja; Garthwaite, Taru; Koivula, Tiia; Laine, Saara; Koivumäki, Mikko; Vähä-Ypyä, Henri; Kallio, Petri; Saarenhovi, Maria; Löyttyniemi, Eliisa; Sievänen, Harri; et al. (Taylor & Francis, 2026)
Background
Lower hemoglobin (Hb) levels within the normal range have been associated with favorable metabolic traits in cross-sectional studies. This study investigated whether changes in Hb levels correlated with changes in physiological and cardiometabolic parameters during a six-month behavioral intervention in individuals with metabolic syndrome.
Methods
The six-month randomized controlled trial aimed to reduce sedentary behavior in adults with metabolic syndrome (n = 64). Key measurements included fasting blood samples, insulin sensitivity during a hyperinsulinemic-euglycemic clamp, insulin-stimulated liver glucose uptake, liver fat content (LFC), indirect calorimetry, cardiorespiratory fitness, and cardiac function. Correlations between changes in these variables and changes in Hb levels at baseline, three, and six months were examined.
Results
Cross-sectionally, higher Hb levels correlated with lower insulin sensitivity (r=-0.35, p = 0.005), higher resting O2 consumption (r = 0.41, p < 0.001), higher resting energy expenditure (r = 0.49, p < 0.001), higher LFC (r = 0.40, p = 0.011), and greater left ventricular wall thickness (r = 0.42, p = 0.001). The intervention did not significantly impact Hb levels, and changes in Hb levels did not correlate with most cardiometabolic changes. However, reduced Hb levels correlated with reduced fasting blood glucose (r = 0.29, p = 0.032), improved insulin sensitivity (r = -0.26, p = 0.045), and increased cardiorespiratory fitness (r = -0.29, p = 0.033).
Conclusions
Changes in Hb levels did not consistently correlate with changes in cardiometabolic markers during the intervention. However, reductions in Hb levels may relate to improved insulin sensitivity and fitness. Along cross-sectional correlations, this may be clinically relevant for individuals with metabolic syndrome. Further studies are merited to clarify the role of Hb levels in this high-risk group.